God behaving badly : is the God of the Old Testament angry, sexist, and racist? - Lamb, David T. (David Trout), 1962- (Downers Grove, Ill. : IVP Books, 2011)
David Lamb unpacks the complexity of the Old Testament to explore the character of God. He provides historical and cultural background to shed light on problematic passages and to bring underlying themes to the fore. Without minimizing the sometimes harsh realities of the biblical record, Lamb assembles an overall portrait that gives coherence to our understanding of God in both the Old and New Testaments.
A bad reputation -- Angry or loving? -- Sexist or affirming? -- Racist or hospitable? -- Violent or peaceful? -- Legalistic or gracious? -- Rigid or flexible? -- Distant or near? -- Epilogue: Is the answer really "Yes, yes and yes"?
Includes bibliographical references (p. [199]-200) and index.
Keywords: God -- Biblical teaching; Bible -- Theology; Apologetics; God -- Biblical teaching; Bible; Apologetics